Antinuclear antibodies in systemic sclerosis associated with increased risk of malignancy - Stochmal, Anna; Sar-Pomian, Marta; Czuwara, Joanna; Rudnicka, Lidia (Dermatology Review/Przegląd Dermatologiczny, 2018)
Patients with systemic sclerosis are at 1.5–5-fold increased risk of developing malignant diseases. It has been shown that some types of antinuclear antibodies associated with systemic sclerosis may have predictive value for development of malignant diseases in patients with systemic sclerosis. Patients with circulating anti-RNA polymerase III antibodies (RNAP) are at significantly increased risk of developing a malignant disease (breast cancer, followed by leukemias and gastrointestinal or gynecologic cancers) within 36 months from the onset of the disease (OR = 7.38). Thus, regular cancer screening is recommended in anti-RNAP III-positive patients. An increased prevalence of lung cancer was reported in patients with circulating anti-topoisomerase I antibodies (11.4%) compared to the median of 2.4% in all patients with systemic sclerosis. Among patients with circulating anti-centromere antibodies, individuals who are anti-CENP-F-positive are at increased risk of developing breast cancer or lung cancer. Anti-PM-Scl antibodies and anti-Ku antibodies are rare in systemic sclerosis, but may have some association with increased risk of malignancy in these patients as well. Thus, recent data indicate that in patients with systemic sclerosis, diverse disease-specific antinuclear antibodies may be associated with increased risk of developing malignant tumors and require especially careful preventive cancer screening.